Carboxylesterase 2 Prevents Liver Steatosis by Modulating Lipolysis, ER stress and Lipogenesis and Is Regulated by HNF4α - Li, Yuanyuan (Hepatology, 2016)
Non-alcoholic fatty liver disease (NAFLD) is a common liver disease that ranges from simple steatosis to non-alcoholic steatohepatitis (NASH). So far, the underlying mechanism remains poorly understood. Here we show that hepatic carboxylesterase 2 (CES2) is markedly reduced in NASH patients, diabetic db/db mice and high fat diet (HFD)-fed mice. Restoration of hepatic CES2 expression in db/db or HFD-fed mice markedly ameliorates liver steatosis and insulin resistance. In contrast, knockdown of hepatic CES2 causes liver steatosis and damage in chow or Western diet-fed C57BL/6 mice. Mechanistically, we demonstrate that CES2 has TG hydrolase activity. As a result, gain of hepatic CES2 function increases fatty acid oxidation and inhibits lipogenesis whereas loss of hepatic CES2 stimulates lipogenesis by inducing ER stress. We further show that loss of hepatic CES2 stimulates lipogenesis in a sterol regulator element-binding protein 1 (SREBP-1)-dependent manner. Finally, we show that hepatocyte nuclear factor 4α (HNF4α) plays a key role in controlling hepatic CES2 expression in diabetes, obesity or NASH. CONCLUSIONS: The current study indicates that CES2 plays a protective role in the development of NAFLD. Targeting the HNF4α-CES2 pathway may be useful for treatment of NAFLD.